1991
DOI: 10.1080/02772249109357672
|View full text |Cite
|
Sign up to set email alerts
|

On the photolysis of selected pesticides in the aquatic environment

Abstract: The photodegradation (UV λ > 290nm) of the herbicides atrazine and diuron was examined in distilled water and artificial seawater containing humic acids. Major photodegradation products were hydroxyatrazine and monuron, respectively. The results showed a faster degradation in seawater as compared to distilled water for atrazine whereas for diuron a quenching effect was observed thus retarding photodegradation. The photodegradation of fenitrothion was also investigated. For this pesticide, the hydrolysis predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Photochemical transformation is one of the main abiotic degradation pathways occurring in natural waters and has received increasing interest in the last thirty years (Addison et al, 1973;Zepp and Cline, 1977;Kotzias and Korte, 1981;Durand et al, 1991;Lemaire et al, 1991;Durand et al, 1992;Scwack et al, 1995;Pirisi et al, 1996;Svenson and Hynning, 1997;Mansour et al, 1999;Méallier, 1999). How persistent these pollutants are in a given environmental system depends on transport and degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical transformation is one of the main abiotic degradation pathways occurring in natural waters and has received increasing interest in the last thirty years (Addison et al, 1973;Zepp and Cline, 1977;Kotzias and Korte, 1981;Durand et al, 1991;Lemaire et al, 1991;Durand et al, 1992;Scwack et al, 1995;Pirisi et al, 1996;Svenson and Hynning, 1997;Mansour et al, 1999;Méallier, 1999). How persistent these pollutants are in a given environmental system depends on transport and degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Photodegradation of pesticides is faster in salt water than in fresh water (Durand et al, 1991;Laws, 1993). Photodegradation of herbicides is enhanced in substrates that contain high concentrations of organic matter and inorganic chemicals that act as photosensitizers (Pelizetti et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Photodegradation of herbicides is enhanced in substrates that contain high concentrations of organic matter and inorganic chemicals that act as photosensitizers (Pelizetti et al, 1992). Various studies have found that the degradation rates are enhanced by the presence of particulate, organic matter, dissolved substances through the attenuation of sunlight, secondary photoreactions, and chemical or physical interactions that change the speciation or availablity of the pesticides (Durand et al, 1991). Kochany and Maguire (1994) reported that the photodegradation of metolachlor was slower in freshwater samples than in distilled water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Photoreduction is generally not very efficient in pure water, but it can be the main reaction in the presence of methanol or other alcohols, which can act as reducing agents, modifying reactivity through hydrogen transfer to the photoactive species. For instance, it has been found that the presence of small percentages of methanol gave rise to photoreduction to monuron 41 or to 3-(3-chlorophenyl)-1,1-dimethylurea. 8 However, it is very unlikely that this is the phototransformation mechanism in the proposed system, since the highest percentage of ethanol used was only 0.1%, whereas the methanol concentrations employed in the studies above cited were around 3 -4%; moreover, additional assays showed that in the presented system the monuron signal was very small.…”
Section: Diuron Photodegradation Mechanismmentioning
confidence: 99%